Evaluation of organic geochemical characteristics and experiments of thermal pressure simulation of Jurassic coal measure source rocks in the Yanqi Basin - Peng, Yicong; Pan, Jishun; Yao, Yaming (Frontiers in Earth Science, 2022)
The Yanqi Basin is a medium-sized coal-bearing basin in western China. In order to find out the hydrocarbon generation potential of the Jurassic source rocks in this area, the organic matter composition of coal-measure mudstone, carbonaceous mudstone and coal, the yields of liquid and gaseous hydrocarbons, and the comparison of oil sources were studied by means of hydrocarbon-generating thermal simulation experiments. The results show that the micro- composition of the Jurassic coal rocks in the Yanqi Basin shows the characteristics of rich vitrinite-inertinite, poor chitinite + saprolite; however, the micro-composition of the mudstone shows the characteristics of poor inertinite and rich vitrinite - chitinite + saprolite. The Jurassic mudstone has a wide distribution range of hydrogen and oxygen indexes, among which the hydrogen index is distributed between 2 and 266 mg/gTOC, and the oxygen index is between 3 and 183 mg/gTOC. The organic matter in the mudstone belongs to Type II2-III kerogen. The hydrogen index of coal is distributed in the range of 100-300 mg/g TOC, which is obviously larger than that of mudstone. The total liquid hydrocarbon yield of the coal rock is the highest (43.2 mg/g.Toc), followed by mudstone (16.4-20.4 mg/g.Toc), and carbonaceous mudstone is the lowest (5.36 mg/g.Toc). In addition, mudstone has the highest yield of gaseous hydrocarbons, followed by coal, while carbonaceous mudstone is the lowest. The oil-source comparison shows that the Jurassic crude oil has a certain affinity with its main source rocks (mudstone, carbonaceous mudstone and coal). At the same time, according to the comparison results of steroid and terpene biomarker parameters with crude oil, it shows that the Middle and Lower Jurassic mudstone, carbonaceous mudstone and coal rock in this area are all source rocks, and the Badaowan Formation mudstone is the main source rock.